2022
DOI: 10.1007/s11071-022-07259-z
|View full text |Cite
|
Sign up to set email alerts
|

Elastic wave propagation in nonlinear two-dimensional acoustic metamaterials

Abstract: This study describes the wave propagation in a periodic lattice which is formed by a spring-mass two-dimensional structure with local Duffing nonlinear resonators. The wave propagation characteristics of the system is evaluated by using the perturbation method and Floquet-Bloch theorem to determine the dispersion relationships and wave propagation characteristics in the nonlinear two-dimensional acoustic metamaterials (2D AM). A quantitative study of wave amplitude is carried out to reveal the limits of the pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 53 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Inspired by the inertial amplification, more and more novel studies are proposed. For instance, an octahedron structure was built to isolate the special omnidirectional elastic waves [40]; incorporating inertial amplification structures in continuous beams to manipulate the transverse wave [41,42]; a 2D thin plates embedded the classical inertial amplifier structures was proposed to modulate lowfrequency and broad lamb waves [43,44]; the low-frequency vibration isolation of the corrugated-core 3 / 26 sandwich panels can be enhanced through embedding the inertial amplification system [45]; a levertype inertial amplification system can achieve the broadband isolation for the surface wave which is induced by the seismic [46,47]; the combination of the inertial amplification and local resonance can improve the extremely narrow effective attenuation of the classical local resonance bandgap [48] and release the dependence on lowering stiffness and increasing mass for low-frequency local resonance bandgap [49]; the multiple, broadband and highly attenuative bandgaps can be obtained by a system with inertial amplification, local resonance, and Bragg scattering affect simultaneously [50]. However, in the last two decades, the design strategies [42,45,[51][52][53][54][55] have been limited to the form of the classical inertial amplification sub-structure.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the inertial amplification, more and more novel studies are proposed. For instance, an octahedron structure was built to isolate the special omnidirectional elastic waves [40]; incorporating inertial amplification structures in continuous beams to manipulate the transverse wave [41,42]; a 2D thin plates embedded the classical inertial amplifier structures was proposed to modulate lowfrequency and broad lamb waves [43,44]; the low-frequency vibration isolation of the corrugated-core 3 / 26 sandwich panels can be enhanced through embedding the inertial amplification system [45]; a levertype inertial amplification system can achieve the broadband isolation for the surface wave which is induced by the seismic [46,47]; the combination of the inertial amplification and local resonance can improve the extremely narrow effective attenuation of the classical local resonance bandgap [48] and release the dependence on lowering stiffness and increasing mass for low-frequency local resonance bandgap [49]; the multiple, broadband and highly attenuative bandgaps can be obtained by a system with inertial amplification, local resonance, and Bragg scattering affect simultaneously [50]. However, in the last two decades, the design strategies [42,45,[51][52][53][54][55] have been limited to the form of the classical inertial amplification sub-structure.…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic metamaterials are artificial subwavelength structures with unconventional dynamic properties and remarkable functions, including local resonance metamaterials, [1][2][3][4][5][6][7][8][9] Helmholtz resonance metamaterials, [3] and membrane-type metamaterials [4,5] and other materials that can effectively achieve low-frequency attenuation, aroused the interest of a large number of researchers. Liu et al [10] used a high-density mass wrapped in a soft rubber material to form a local resonance unit using a simple cubic lattice form and Zhao et al [11] studied the dispersion relationship and wave propagation properties in nonlinear resonator two-dimensional acoustic metamaterials, and the results can be used to tune wave propagation in nonlinear acoustic metamaterials, providing some ideas for nonlinear research. The propagation of elastic waves in origami-inspired lattices was also studied, and it was found that origami-inspired lattices provided a new method for designing vibration-isolating structures.…”
Section: Introductionmentioning
confidence: 99%